2014
DOI: 10.5489/cuaj.1970
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer screening characteristics in men with BRCA1/2 mutations attending a high-risk prevention clinic

Abstract: Introduction: The prostate-specific antigen (PSA) era and resultant early detection of prostate cancer has presented clinicians with the challenge of distinguishing indolent from aggressive tumours. Mutations in the BRCA1/2 genes have been associated with prostate cancer risk and prognosis. We describe the prostate cancer screening characteristics of BRCA1/2 mutation carriers, who may be classified as genetically-defined high risk, as compared to another high-risk cohort of men with a family history of prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…The MEDLINE database query resulted in 289 studies, of which 12 met inclusion criteria (Table ). Mitra et al consisted of preliminary findings that were later reported in the Bancroft et al study, so it was not included in the analysis .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MEDLINE database query resulted in 289 studies, of which 12 met inclusion criteria (Table ). Mitra et al consisted of preliminary findings that were later reported in the Bancroft et al study, so it was not included in the analysis .…”
Section: Resultsmentioning
confidence: 99%
“…The data extracted from each study included year of publication, study type, population of interest, identified mutations, age, PSA level, GS, tumor stage, and outcomes data of overall and cause‐specific survival. Tumor stage was determined by clinical and surgical findings. Chi‐squared statistics and P ‐values were calculated to compare GS and stage among retrospective and prospective studies , as well as by average age groupings (<65 vs. >65 years ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical environment of blood-based biomarker studies it has been shown that a single biomarker is generally not effective in detecting or guiding management and detection of disease, and that panels of multiple biomarkers are required [ 15 19 ]. Protein blood biomarkers such as carcinoembryonic antigen (CEA), cancer antigen 19–9 (CA19-9) and prostate specific antigen (PSA) used in this study, have been widely studied for many decades and are used in mainstream clinical disease management [ 20 24 ]. Endothelin-1, cancer antigen 125 (CA125) and cancer antigen 15–3 (CA15-3) have been studied in uterine fibroids [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Um biomarcador é definido como uma molécula ou outro dado que caracteriza um processo biológico em estado normal e patológico, sendo que sua expressão se diferencia ou só é estabelecida em estado patológico. Logo, é uma ferramenta importante, utilizada para se Nossa hipótese a respeito do PSA, que ainda é um método de intensa controvérsia, pode ser sustentada pelo fato do PSA não ser considerado câncer específico, podendo estar alterado em outros processos patológicos da próstata, reforçando a ideia de que o aumento do PSA visto em tumores da próstata não esteja diretamente relacionado ao processo neoplásico, diminuindo a confiabilidade da utilização do PSA no diagnóstico prostático, fato que tem sido cada vez mais sugerido por estudiosos da área(56)(57)(58)(59)(60). Gleason =7, apresentaram expressão positiva para o marcador em questão.…”
unclassified